1989
DOI: 10.1128/mcb.9.11.5123
|View full text |Cite
|
Sign up to set email alerts
|

A nuclease-hypersensitive element of the human c-myc promoter interacts with a transcription initiation factor.

Abstract: Transcription of the human c-myc oncogene is elaborately regulated, but the relevant molecular mechanisms are not yet understood. To begin to define elements and enzyme systems responsible for c-myc transcription in vitro, we partially purified a transcription factor essential for efficient and accurate in vitro initiation from the principal myc promoter, P2. DNA mobility shift assays located the factor binding domain at -142 to -115 with respect to the P1 promoter. This region contains pur/pyr sequences (pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
120
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(124 citation statements)
references
References 50 publications
(67 reference statements)
4
120
0
Order By: Relevance
“…1A). This fragment contains the c-myc P 0 and P 1 promoters, several transcription factor consensus binding sites, and an organized nucleosome array stable with respect to chromosomal translocation (20,35,37,44,45,67,71,78,87). To analyze the effect of transcription on replicator activity, clonal cell lines were constructed using the yeast FLP recombinase to integrate donor plasmids containing wild-type or mutated versions of the c-myc core replicator in the FRT site in the HeLa/ 406 acceptor cell line (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1A). This fragment contains the c-myc P 0 and P 1 promoters, several transcription factor consensus binding sites, and an organized nucleosome array stable with respect to chromosomal translocation (20,35,37,44,45,67,71,78,87). To analyze the effect of transcription on replicator activity, clonal cell lines were constructed using the yeast FLP recombinase to integrate donor plasmids containing wild-type or mutated versions of the c-myc core replicator in the FRT site in the HeLa/ 406 acceptor cell line (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We (23), and H4TF-1 (5) have DNA recognition sites that are similar to those of suGF1 but have been shown to be proteins larger than 100 kDa. Other factors implicated in human c-myc gene regulation appear to differ from suGFl in that they do not result in a DNase I footprint on their G-rich recognition site (factor PuF [29]) or are associated with RNA (factor NSE [6]). The biochemical and DNA-binding properties of suGF1 are remarkably similar to those of BGP1, the chicken factor implicated in PA-globin gene expression (4,22).…”
Section: Figmentioning
confidence: 99%
“…We have shown that suGF1 has a DNA-binding specificity similar to those of several factors which recognize G-rich sequences within the context of pur. pyr stretches upstream of genes (6,9,12,24,29,34). In addition, several of these factors have been implicated in gene regulation via alterations in chromatin structure within the pur-pyr region (see the introduction).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of positive and negative elements has been identified within the regulatory region of the c-myc promoters with potential binding sites for the transcription factors NF1/CTF, SP1, E2F, Ap1, OCT, PRF, PuF, NFB, YY1, Maz, FBP, LR1, hu-CUT, CTCF, and others (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22), for reviews, see Refs. 1 and 2.…”
mentioning
confidence: 99%